Bacterial overgrowth assessment and treatment among pediatric intestinal rehabilitation and nutrition support providers: An international survey of clinical practice patterns. Issue 8 (30th March 2022) - Namjoshi, Shweta S.; Galloway, David; Herdes, Rachel E.; Talathi, Saurabh; Ding, Victoria Y.; Mezoff, Ethan A.
Abstract: Background: Small bowel bacterial overgrowth (SBBO) is a common, but difficult to diagnose and treat, problem in pediatric short bowel syndrome (SBS). Lack of clinical consensus criteria and unknown sensitivity and specificity of bedside diagnosis makes research on this potential SBS disease modifier challenging. The objective of this research was to describe clinical care of SBBO among international intestinal rehabilitation and nutrition support (IR&NS) providers treating patients with SBS. Methods: A secure, confidential, international, electronic survey of IR&NS practitioners was conducted between March 2021 and May 2021. All analyses were conducted in the R statistical computing framework, version 4.0. Results: Sixty percent of respondents agreed and 0% strongly disagreed that abdominal pain, distension, emesis, diarrhea, and malodorous stool, were attributable to SBBO. No more than 20% of respondents strongly agreed and no more than 40% agreed that any sign or symptom was specific for SBBO. For a first‐time diagnosis, 31 practitioners agreed with use of a 7‐day course of a single antibiotic, with a majority citing grade 5 evidence to inform their decisions (case series, uncontrolled studies, or expert opinion). The most common first antibiotic used to treat a new onset SBBO was metronidazole, and rifaximin was the second most commonly used. One hundred percent of respondents reported they would consider a consensus algorithm for SBBO, even if the algorithm may be divergent from their current practice. Conclusion: SBBO practice varies widely among experienced IR&NS providers. Development of a clinical consensus algorithm may help standardize care to improve research and care of this complex problem and to identify risks and benefits of chronic antibiotic use in SBS.